Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(\frac{5}{11}\times\frac{7}{25}+\frac{15}{11}\times\frac{1}{5}\)
\(=\frac{5}{11}\times\frac{7}{25}+\frac{5}{11}\times\frac{3}{5}\)
\(=\frac{5}{11}\times\left(\frac{7}{25}+\frac{3}{5}\right)\)
\(=\frac{5}{11}\times\frac{22}{25}\)
\(=\frac{2}{5}\)
b, \(\frac{3}{7}\times\frac{25}{19}-\frac{1}{7}\times\frac{18}{19}\)
\(=\frac{1}{7}\times\frac{75}{19}-\frac{1}{7}\times\frac{18}{19}\)
\(=\frac{1}{7}\times\left(\frac{75}{19}-\frac{18}{19}\right)\)
\(=\frac{1}{7}\times3\)
\(=\frac{3}{7}\)
\(\frac{9}{22}\)và \(\frac{3}{11}\)
Ta có : \(\frac{3}{11}=\frac{6}{22}\)
\(\frac{9}{22}+\frac{6}{22}=\frac{15}{22}\)
Ủng hộ nhé !
\(\frac{1}{2}:\frac{3}{2}:\frac{5}{4}:\frac{6}{5}:\frac{7}{6}:\frac{8}{7}\)
\(=\frac{1}{2}\cdot\frac{2}{3}\cdot\frac{4}{5}\cdot\frac{5}{6}\cdot\frac{6}{7}\cdot\frac{7}{8}\)
\(=\frac{1\cdot\left(2\cdot5\cdot6\cdot7\right)}{8\cdot3\cdot\left(2\cdot5\cdot6\cdot7\right)}\)
\(=\frac{1}{24}\)
\(\frac{1}{2}\cdot\frac{2}{3}\cdot\frac{3}{4}\cdot\frac{4}{5}\cdot\frac{5}{6}\cdot\frac{6}{7}\cdot\frac{7}{8}\cdot\frac{8}{9}\cdot\frac{9}{10}\)
\(=\frac{1\cdot\left(2\cdot3\cdot4\cdot5\cdot6\cdot7\cdot8\cdot9\right)}{\left(2\cdot3\cdot4\cdot5\cdot6\cdot7\cdot8\cdot9\right)\cdot10}\)
\(=\frac{1}{10}\)
\(\frac{9}{8}>\frac{8}{9}\)
\(\frac{16}{23}>\frac{16}{25}\)
\(\frac{8}{11}< \frac{8}{10}\)
\(\frac{10}{13}>\frac{19}{26}\)
\(\frac{13}{15}< \frac{11}{10}\)
\(\frac{11}{9}=\frac{44}{36}\)
9/8 > 8/9
16/23 > 16/25
8/11 < 8/10
10/13 > 19/26
13/15 < 11/10
11/9 = 44/36
Tham khảo nha !
Chúc bạn học giỏi !
\(a.\) \(\frac{4}{15}.\frac{7}{9}+\frac{4}{15}.\frac{2}{9}\)
\(=\frac{4}{15}\left(\frac{7}{9}+\frac{2}{9}\right)\)
\(=\frac{4}{15}.\frac{9}{9}\)
\(=\frac{4}{15}.1\)
\(=\frac{4}{15}\)
\(b.\) \(\frac{13}{19}.\frac{23}{11}-\frac{13}{19}.\frac{8}{11}-\frac{13}{19}.\frac{4}{11}\)
\(=\frac{13}{19}\left(\frac{23}{11}-\frac{8}{11}-\frac{4}{11}\right)\)
\(=\frac{13}{19}.\frac{11}{11}\)
\(=\frac{13}{19}.1\)
\(=\frac{13}{19}\)
a)4/15 x(7/9+2/9)=4/15x1=4/15
b)13/19x(23/11-8/11-4/11)13/19x1=13/19
\(a.\frac{4}{3}-\frac{3}{2}:X=\frac{1}{6}\)
\(\frac{3}{2}:X=\frac{4}{3}-\frac{1}{6}\)
\(\frac{3}{2}:X=\frac{8}{6}-\frac{1}{6}\)
\(\frac{3}{2}:X=\frac{7}{6}\)
\(X=\frac{3}{2}:\frac{7}{6}\)
\(X=\frac{3}{2}\times\frac{6}{7}\)
\(X=\frac{9}{7}\)
\(b.\left(X+\frac{2}{3}\right):\frac{1}{3}=\frac{41}{3}\)
\(X-\frac{2}{3}=\frac{41}{3}.\frac{1}{3}\)
\(X-\frac{2}{3}=\frac{41}{9}\)
\(X=\frac{41}{9}+\frac{2}{3}\)
\(X=\frac{41}{9}+\frac{6}{9}\)
\(X=\frac{47}{9}\)
A=49/50
\(A=\frac{7}{1\cdot8}+\frac{11}{8\cdot19}+\frac{22}{19\cdot41}+\frac{9}{41\cdot50}\)
\(A=1-\frac{1}{8}+\frac{1}{8}-\frac{1}{19}+\frac{1}{19}-\frac{1}{41}+\frac{1}{41}-\frac{1}{50}\)
\(A=1-\frac{1}{50}=\frac{49}{50}\)